Psychometric Properties of the Indonesian Version of Impact of Event Scale-Revised Questionnaire During COVID-19 Pandemic - Wijovi, Felix; Kurniawan, Andree; Lugito, Nata Pratama Hardjo; Agung, Fransisca Handy; Cipta, Darien Alfa; Angelina, Stella; Halim, Devina Adella; Jodhinata, Claudia; Orlin, Sisilia; Hamdoyo, Audrey; Evangelista, Nadya Nathalia (Fakultas Kedokteran Universitas Pelita Harapan, 2021)
Background: COVID-19 is a respiratory infection caused by SARS CoV-2. A health-related disaster may result in a wide range of mental consequences, including PTSD. IES-R is a self-reported instrument, and it corresponds to DSM-IV symptoms of PTSD. However, there were scarce data about the validation of the Indonesian version of IESR.Aim: The purpose of this study was to validate the IES-R in the Indonesian adult population by comprehensively and systematically assessing the epidemiological evidence about PTSS during the COVID-19 pandemic.Methods: This was a cross-sectional study. The IES-R questionnaire was translated from English to Indonesian, back-translated. All health workers were excluded to avoid the biased result. Pearson correlation and Cronbach's alpha coefficients to determine the validity and reliability of the questionnaire.Results: A total of 234 Indonesian-speaking adults completed the survey. The Indonesian IES-R had proven to be a valid (r= 0.756 -0.938, p= 0.000) and reliable (alpha coefficient: 0.858-0.868) measure for PTSS in a sample of Indonesian adults during the COVID-19 pandemic. In addition, the final model which consisted of 3 subscales with 20 items demonstrated acceptable factor loadings.Conclusion: The results of this study suggested IESR is valid and reliable to be used in the Indonesian population especially during pandemics.